Keanekaragaman Vegetasi Mangrove di Kawasan Hutan Mangrove Taman Nasional Karimunjawa, Kabupaten Jepara, Jawa Tengah - Roni Sipayung (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
This study aims to determine the density of mangrove vegetation found in mangrove forest areas. This research was conducted in the Mangrove Forest Area of ​​Karimunjawa National Park, Jepara Regency, Central Java. Retrieval of research data using a systematic path with a total of 75 plots in the entire Mangrove Forest Area of ​​Karimunjawa National Park with nested sampling method. Using this method, the number of species and vegetation density values ​​were obtained in the form of seedling density, sapling density, and tree density. Data analysis used quantitative description in the form of a graph of mangrove vegetation density. The results showed that the density of vegetation in the Mangrove Area of ​​Karimunjawa National Park, Jepara Regency, Central Java was classified as moderate. The vegetation density values ​​for block A at the growth rate of seedlings, saplings and trees were 13103.45 individuals/ha, 2096.55 individuals/ha and 331.03 individuals/ha while the density of mangrove vegetation for block B at the growth rate of seedlings, saplings, and trees respectively, namely 23478.26 individuals/ha, 3756.52 individuals/ha, and 217.39 individuals/ha.The diversity index value in block A was 1.797 while in block B it was 2.110.